ECONOMIC VALUE ADDED (EVA) AND FINANCIAL VALUE ADDED (FVA) ANALYSIS OF PUBLIC COMPANY CARRYING MERGER IN 2006 - Budi`, Ari (Jurnal Analisis Bisnis Ekonomi, 2012)
This research is aimed to observe EVA and FVA value of public company carrying merger on 2006,which are PT Akasha Wira International Tbk (ADES), PT Surya Toto Tbk (TOTO), and PT Selamat Sempurna Tbk (SMSM), by comparing the EVA and FVA value and its changes before and after the merger. EVA is a concept of measuring value created by the firm to the shareholder, by subtracting cost of capital from NOPAT (Net Operating Profit after Tax). The second variable is FVA which is to measure the value created for the shareholder from the view of fixed asset contribution. This research evidenced that the three companies raised their EVA and FVA 1 ? 2 years after the merger.